Area Deprivation as a Risk Factor for Methicillin-resistant Staphylococcus aureus Infection in Pediatric Cystic Fibrosis. Issue 11 (November 2019) - Oates, Gabriela R.; Harris, William T.; Rowe, Steven M.; Solomon, George M.; Dey, Suranjana; Zhu, Aowen; Hoover, Wynton C.; Gutierrez, Hector H.
Abstract : Background: In US cystic fibrosis (CF) patients, methicillin-resistant Staphylococcus aureus (MRSA) rates have tripled in the past 2 decades. Known clinical risk factors include exposure to a healthcare setting, Pseudomonas aeruginosa and CF-related diabetes. Area-level socio-environmental exposures have not been evaluated. We explored the association of area-level deprivation with MRSA prevalence in a pediatric CF Center in the Southeastern United States. Methods: Patients' residential addresses were geocoded and linked to a composite Area Deprivation Index and Rural-Urban Commuting Area scores. The association of MRSA with Area Deprivation Index and Rural-Urban Commuting Area scores was evaluated using logistic regression with robust standard errors adjusted for sociodemographic covariates (age, sex, race, mother's and father's education and household income), clinical risk factors ( P. aeruginosa, CF-related diabetes, hospitalizations and number of clinic visits) and clustering. Results: The study included all pediatric patients (N = 231; mean age 12) at a single CF Center. MRSA was present in 44% of subjects. Higher area-level deprivation was correlated with rural residence, lack of parental college education and lower household income ( P < 0.001 for each). In a multiple regression model fully adjusted for patient-level sociodemographic covariates, clinical risk factors and clustering, neighborhood deprivation was associated with more than 2-fold increase in the odds of having MRSA [OR 2.26 (1.14–4.45), P < 0.05]. Conclusions: Neighborhood deprivation is a risk factor for MRSA in pediatric CF, doubling the odds of infection. Community-level socioeconomic risk factors should be considered when developing prevention strategies and treatment plans for MRSA infection in pediatric patients with CF.